EFFECT OF ETHANOL CONCENTRATION OF LIQUORICE EXTRACT (Glycyrrhiza glabra L.) IN SUNSCREEN BODY LOTION PREPARATIONS TOPHYSICAL PROPERTIES, PHYSICAL STABILITY AND ANTIOXIDANT ACTIVITY (SPF) - Seftiani, Dita; Paloma, Yacinta (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2023)
AbstractLiquorice (Glycyrrhiza glabra L.) is a plant that has an interactive effect of UV protective, antiinflammatory & antioxidant activity responsible for exerting useful effects on the skin. Liquorice contains chemical components such as sugars, flavonoids, sterols, starch, amino acids, essential oil resins and saponins.This study aims to determine the effect of sweet root extract (Glycyrrhiza glabra L.) to the value of sun protection factor (SPF), physical properties and physical stability of sunscreen body lotion preparations. Preparation of Body lotion Sunscreen liquorice extract made five formulas with variations in concentration 7.5%; 12%; 15%; 18%; and 20%. Then conducted phytochemical screening terjadap sweet root extract, the made the formulation of Body lotion Sunscreen sweet root extract (Glycyrrhiza glabra L.), then measured the SPF value of the preparation of sunscreen body lotion sweet root extract (Glycyrrhiza glabra L.) with UV spectrophotometer. Physical properties such as viscosity, pH, adhesion and dispersion tests were tested by linear regression. Physical stability (viscosity test, pH test, dispersion and adhesion test) analysis using Anova one way test method. Determination of SPF value, organoleptic test, homogeneity and emulsion type descriptively. Physical properties of the five formulas have a characteristic liquorice odor, lotion shape, yellowish brown color on F1 and dark brown on F2, F3, F4 and F5, preparation of a homogeneous liquorice extract body lotion. The higher the concentration of the extract in the body lotion, the viscosity and adhesion increased, while the pH and dispersion decreased. Physical stability of the five formulas with concentrations of FI (7.5%), FII (12%), F3 (15%), F4 (18%) and F5 (20%) stable in terms of homogeneity test and organoleptic tests include odor,shape and color of FI (7.5%) on days 0 and 7 stable, but lotion on Days 14, 21 and 28 oxidation with discoloration or unstable. The five formulations on viscosity, pH, adhesion and dispersibility tests during 28-day storage at room temperature 270C were unstable. Liquorice extract (Glycyrrhiza glabra L.) with variations in concentration F1(7.5%); F2 (12%); F3 (15%); F4 (18%) and F5 (20%) have Sun Protection Factor (SPF) values respectively 1.72; 17.83; 21.17; 23.32 and 32.32, the five formulas are included in the ultra Protection category range (>15).Keywords: Sweet Root, Body Lotion, Sun Protection Factor (SPF)